Quantitative Changes in the Mitochondrial Proteome of Cerebellar Synaptosomes From Preclinical Cystatin B-Deficient Mice - Gorski, Katarin; Spoljaric, Albert; Nyman, Tuula A.; Kaila, Kai; Battersby, Brendan J.; Lehesjoki, Anna-Elina (Frontiers in Molecular Neuroscience, 2020)
Progressive myoclonus epilepsy of Unverricht-Lundborg type (EPM1) is a neurodegenerative disorder caused by loss-of-function mutations in the cystatin B (CSTB) gene. Progression of the clinical symptoms in EPM1 patients, including stimulus-sensitive myoclonus, tonic-clonic seizures, and ataxia, are well described. However, the cellular dysfunction during the presymptomatic phase that precedes the disease onset is not understood. CSTB deficiency leads to alterations in GABAergic signaling, and causes early neuroinflammation followed by progressive neurodegeneration in brains of a mouse model, manifesting as progressive myoclonus and ataxia. Here, we report the first proteome atlas from cerebellar synaptosomes of presymptomatic Cstb-deficient mice, and propose that early mitochondrial dysfunction is important to the pathogenesis of altered synaptic function in EPM1. A decreased sodium-and chloride dependent GABA transporter 1 (GAT-1) abundance was noted in synaptosomes with CSTB deficiency, but no functional difference was seen between the two genotypes in electrophysiological experiments with pharmacological block of GAT-1. Collectively, our findings provide novel insights into the early onset and pathogenesis of CSTB deficiency, and reveal greater complexity to the molecular pathogenesis of EPM1.